2017
DOI: 10.1103/physics.10.77
|View full text |Cite
|
Sign up to set email alerts
|

Tube Model Under Tension

Abstract: The flow and deformation of macromolecules is ubiquitous in nature and industry, and an understanding of this phenomenon at both macroscopic and microscopic length scales is of fundamental and practical importance. Here, we present the formulation of a general mathematical framework, which could be used to extract, from scattering experiments, the molecular relaxation of deformed polymers. By combining and modestly extending several key conceptual ingredients in the literature, we show how the anisotropic sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 133 publications
0
4
0
Order By: Relevance
“…Our additional analysis of the mean-square internal separation in both the parallel and perpendicular directions indicates the absence of nonmonotonic features at all length scales. Considering the unmistakable, monotonic trend revealed by the current simulation, we reason that it is unlikely for NEMD simulations on a larger, more entangled system to produce qualitatively different results . Lastly, it is worth noting that a previous NEMD simulation study of unentangled polymer melts also reported a monotonic change of the radius of gyration tensor during the stress relaxation after a large step deformation …”
mentioning
confidence: 57%
See 3 more Smart Citations
“…Our additional analysis of the mean-square internal separation in both the parallel and perpendicular directions indicates the absence of nonmonotonic features at all length scales. Considering the unmistakable, monotonic trend revealed by the current simulation, we reason that it is unlikely for NEMD simulations on a larger, more entangled system to produce qualitatively different results . Lastly, it is worth noting that a previous NEMD simulation study of unentangled polymer melts also reported a monotonic change of the radius of gyration tensor during the stress relaxation after a large step deformation …”
mentioning
confidence: 57%
“…Considering the unmistakable, monotonic trend revealed by the current simulation, we reason that it is unlikely for NEMD simulations on a larger, more entangled system to produce qualitatively different results. 25 Lastly, it is worth noting that a previous NEMD simulation study of unentangled polymer melts also reported a monotonic change of the radius of gyration tensor during the stress relaxation after a large step deformation. 50 In summary, we have performed large-scale nonequilibrium molecular dynamics simulations on well-entangled polymers to critically test the chain retraction hypothesis of the nonlinear tube theory.…”
Section: Acs Macro Lettersmentioning
confidence: 82%
See 2 more Smart Citations